The feminist discourse and the case of Women of Zimbabwe Arise (WOZA) - Mapuva, Loveness Muyengwa (International Knowledge Sharing Platform, 2016)
Literature on women and gender has sought to present the violation of women’s rights from a patriarchal perspective. Through international instruments, recognition of women have been collaborated. The rise of feminist civil society organisation seeking to influence policy decisions at international, regional and national levels have emerged. In Zimbabwe, the role played by women in the socio-economic development of the country have shown the indispensable role of women in society. Through Women of Zimbabwe Arise, this paper discusses the role that WOZA has played in articulating the role of women in nation building through the observance of their right.